Pengembangan E-Modul Interaktif Berbasis Pendekatan STEAM Pada Pembelajaran Matematika di Kelas V Sekolah Dasar - Wahyuningsih Wahyuningsih; Melva Zainil; Salmaini Salmaini; Syofianti Engreini (Universitas Negeri Padang, 2025)
This study was conducted due to the limited integration of interactive digital teaching materials in fifth-grade mathematics learning, which has led to low student engagement and suboptimal learning outcomes. Mathematics instruction is still predominantly delivered through printed modules and conventional methods, limiting students’ opportunities to actively explore concepts. Therefore, developing innovative and student-centered digital learning resources is essential. This study aimed to develop a STEAM-based interactive e-module that is valid, practical, and effective for teaching nets of cubes and rectangular prisms in accordance with the Merdeka Curriculum. This research employed the Research and Development (R&D) method using the ADDIE model. The subjects were fifth-grade students from SDN 24 and SDN 12 Pincuran Tujuah. Data were collected through expert validation, practicality questionnaires, and pretest–posttest assessments. The results showed that the e-module achieved a very high level of validity, with scores from media experts (90.52%), material experts (94%), and language experts (95.55%). Practicality results indicated very high responses from teachers (97.69%) and students (96.98%). Effectiveness testing showed a significant improvement in learning outcomes, with a high N-Gain Score. Thus, the developed e-module is valid, practical, and effective for enhancing mathematics learning.